Intraosseous Lipomatous Meningioma - Lauren Kim; Christopher Huang; Adrienne L. Morey; Mark J. Winder (Case Reports in Neurological Medicine)
A 49-year-old man with intermittent headaches and right sided parietal lump was found to have an intraosseous right parietal lesion on computed tomography (CT) and magnetic resonance imaging (MRI). A stereotactic craniectomy and excision of the lesion were performed with histopathology confirming features consistent with primary lipomatous meningioma with intraosseous extension. Lipomatous meningiomas are very uncommon subtype of meningiomas, with ongoing discussions as to their true pathogenesis. To our knowledge this case represents the first reported case of a lipomatous meningioma with predominant intraosseous extension.